Pengaruh Penggunaan Strategi SQ3R dengan Variasi Tebak Kata terhadap Hasil Belajar Biologi Siswa Kelas XI SMAN 3 Kota Solok - Mona Gumala Sari; Asmawati Kamal; Darmanella Dian Eka Wati (Eduscience Development Journal, 2020)
During the learning process often encountered lack of activity, interest and motivation of students. Students tend to be individual in learning, students are not trained to work together with other friends, it can be seen from each execution group discussions. In addition to the learning process of teachers tend to use the lecture method monotonous, accept what is described by teachers that have an impact on student learning outcomes much lower. The formulation of the problem in this study whether learning SQ3R with guess the word effect on learning outcomes in class XI SMAN 3 Kota Solok?. This study aimed to determine the effect of learning SQ3R with guess the word on learning outcomes biology in class XI SMAN 3 Kota Solok. The hypothesis in this study is SQ3R with guess the word affect the biology of learning outcomes in class XI SMAN 3 Kota Solok. Data analysis was conducted of student learning outcomes obtained zcount = 2,10 and ztable = 1,67 indicates that the zcount > ztable then H0 is rejected hypothesis H1 is accepted at 95 % confidence level. It can be concluded that the learning SQ3R with guess the word the biology of learning outcomes SMAN 3 Kota Solok, where the average value of the class with the learning SQ3R with guess the word is higher than the learning SQ3R without using guess the word.